DYNAMICS OF RIPENING OF AFUS-ALI TABLE GRAPE VARIETY - Boskov, K.; Doneva Sapceska, D.; Kryeziu, S.; Božinovik, Z.; Hristov, P.; Prculovski, Z. (JAFES, 2017)
The afus-ali variety, together with the muscat italia, cardinal, victoria, ribier, and palieri, is the most important table grape variety in the Republic of Macedonia. We studied the dynamics of ripening of the afus-ali table grape variety from two locations Kavadarci and Valandovo where this variety is most commonly cultivated in the Republic of Macedonia. To determine the timing of ripening, we examined the dynamics of ripening by randomised sampling in the period from early August to the ripening of the grapes in early September. Four samples with three repetitions for each sample were taken every 10 days. We analysed the mechanical and chemical composition and mechanical properties of the cluster and berries following the OIV (International Organisation of Vine and Wine) methods. We used statistical analysis of the completely randomised design. The changes that occur during ripening of the afus-ali variety are the indicator of its technological ripeness. The results can be applied in the planning of the vintage depending on the market placement and duration of refrigerator storage of grapes.
Keywords: table grape variety, afus-ali, dynamics, ripening